(untitled) (Texas Journal of Multidisciplinary Studies, 2024)
In criminal law theory, a more detailed characterization of the characteristics of continuous crimes has been developed, and for the purpose of scientific analysis, they are divided into several specific objective (the presence of two or more independent actions, committed at different times) and subjective (covered by a single intent, directed towards a single goal) characteristics.